Unpacking the Sport Education Model (SEM) in Indonesia: a systematic review of implementation and impact - Widiyatmoko, Fajar; Setiawan, Caly; Hamid, Muhammad Anwar; Pradipta, Galih Dwi (Edu Sportivo: Indonesian Journal of Physical Education, 2025)
Background: Research on pedagogical models in physical education has increased rapidly in the past two decades, with the Sport Education Model (SEM) being the most dominant approach. However, systematic mapping for SEM implementation in Indonesia is limited. Research Objectives: This study aims to critically examine the application of SEM in Indonesia to provide a more comprehensive and up-to-date picture. Methods: The articles used for analysis were initially sourced from the Scopus, Web of Science, and Sinta databases. We conducted the search according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Review studies meeting the following inclusion criteria: (1) Peer-reviewed journal articles published and written in Indonesian or English between 2015 and 2024, (2) Included participants from elementary, middle and high schools and colleges, (3) Conducted in the physical education context, and (4) Intervention studies implementing one, several or combined pedagogical models. Exclusion criteria were: (1) Not scientific review studies and (2) Not about SEM implementation. After the exclusion criteria, only 17 articles were categorised, all published between 2015 and 2024. Findings/Results: A total of 17 articles involving 1,184 students were analysed. Interventions lasted between 8 and 16 meetings per semester, with the content dominated by invasion games (football, handball, basketball) and net games (badminton, volleyball). The research design was largely experimental, although not all used a control group. Variables tested included motivation, leadership, game play, tactical awareness, and sport orientation. Conclusions: SEM was found to be effective in enhancing student learning across multiple domains (cognitive, social, physical, and affective). However, we identified weaknesses in the lack of exploration of individualised sports, limitations in methodological design, and narrow coverage of variables. This study emphasises the need for diverse approaches and further exploration in local contexts.